Developing an Electronic Dictionary of Elements and Compounds in Chemistry to Improve the Tenth Graders‟ Pronunciation - Ibnu, Mat ((JELE) Journal Of English Language and Education, 2015)
Inaccessibility of electronic dictionaries for learning pronunciation of elementsand compounds in Chemistry was found at Semarang State Senior High School 2. Theobserved inaccessibility came from the Chemistry teacher who shared her problemsthat her students got difficulties in pronouncing elements and compounds. Then, theexisting electronic dictionaries were lack of the words they needed. Hence, this studywould like to develop an Electronic Dictionary of Elements and Compounds inChemistry (EDECC) for assisting students, notably the tenth graders of SemarangState Senior High School 2, to improve their pronunciation in learning elements andcompounds. This study employed Research and Development design to develop theEDECC. This design was adopted and modified fromBorg and Gall (2003:772). Sevenstages were employed for developing EDECC were information and research collecting,planning, developing, validating, revising, try out, and producing final EDECC.Observation, interview, validation, and pre-test also post-test were administered tocollect the data while both quantitative and qualitative approaches were used toanalyze the collected data. From the result of observations, questionnaires, validation,interviews, and pre-test and post-testwere found that applying the EDECC gainedpositive perspectives toward teaching and learning process.Moreover, the test ofeffectiveness consisting validity and reliability tests on pretest and posttest employingquasi experimental design reported that there was significant difference between theresult of pretest and posttest. It means that all the result of collected data agreed thatthe EDECC could be implemented in improving the students‟ pronunciation.Keywords : Electronic Dictionary, Teaching Pronunciation, Chemical Elements andCompounds